Pengaruh Struktur Kepemilikan Dan Ukuran Perusahaan Terhadap Pengungkapan Manajemen Risiko - Edo Bangkit Prayoga; Luciana Spica Almilia (Universitas Bandar Lampung (UBL), 2013)
Every company inevitably face risk in terms of financial risk or operational risk. In an uncertain economic situation, risk management is one way to reduce and deal with any risk that the company may face. This study aimed to analyze the effect of managerial ownership, domestic institutional ownership, foreign institutional ownership, public ownership and firm size on theÂ risk management disclosure. The population used here was secondary data from the Indonesia Stock Exchange (BEI), i.e.Â the annual reports of listed manufacturing companies in periods of the year 2007-2011. The sample study using purposive sampling and final data consisted of 189 companies. The statistical method used is multiple regression analysis, hipotesis test by t test and F test. the results of this study indicate that (1) managerial ownership has no effect on risk management disclosure (2) domestic institutional ownership affects the disclosure of risk management (3) foreign institutional ownership affects the risk management disclosure (4) public ownership affect the disclosure of risk management (5) does not affect the size of the companys risk management disclosures.